2016
DOI: 10.1111/jcal.12140
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding wiki‐supported collaborative learning for small‐group projects and whole‐class collaborative knowledge building

Abstract: While educators value wikis' potential, wikis may fail to support collaborative constructive learning without careful scaffolding. This article proposes literature-based instructional methods, revised based on two expert instructors' input, presents the collected empirical evidence on the effects of these methods and proposes directions for future refinements. The instructional methods were implemented by an expert instructor teaching a 12-week 68-student undergraduate design class in Canada. Data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…These results showed the positive effect of structured scripts for meaningful negotiation when addressing a complex task (Haake & Pfister, 2010;Weinberger, Stegmann, Fischer, & Mandl, 2007). Still, not many studies have investigated appropriate methods for systematically supporting learners' negotiation processes to encourage them to propose diverse ideas and integrate feedback into one solution to reach a collaborative outcome in CSCL environments (see Lin & Reigeluth, 2016;Tiruneh et al, 2016). It is unclear how scaffolding strategy should be effectively differentiated in the meaning-negotiation phase and position-negotiation phase, given the characteristics of scaffolding (Shin et al, 2018;Slof et al, 2010).…”
Section: Negotiation Scaffoldingmentioning
confidence: 98%
“…These results showed the positive effect of structured scripts for meaningful negotiation when addressing a complex task (Haake & Pfister, 2010;Weinberger, Stegmann, Fischer, & Mandl, 2007). Still, not many studies have investigated appropriate methods for systematically supporting learners' negotiation processes to encourage them to propose diverse ideas and integrate feedback into one solution to reach a collaborative outcome in CSCL environments (see Lin & Reigeluth, 2016;Tiruneh et al, 2016). It is unclear how scaffolding strategy should be effectively differentiated in the meaning-negotiation phase and position-negotiation phase, given the characteristics of scaffolding (Shin et al, 2018;Slof et al, 2010).…”
Section: Negotiation Scaffoldingmentioning
confidence: 98%
“…Several studies have focused on the use of social media, in particular wikis, to promote learning objectives including student collaboration, knowledge building, writing skills, and scientific literacy. Wikis (i.e., publicly editable websites with informative articles) are commonly used by educators as tools to foster student collaboration (Hulbert-Williams, 2010; Kummer, 2013;Shane-Simpson et al, 2016;Zheng et al, 2015) and knowledge building, or the "collective creation of public knowledge" (Kimmerle et al, 2011, p. 139;Lin & Reigeluth, 2016, 2019). Kummer's (2013) meta-analysis on wiki collaboration indicated that providing wiki training, incentivizing participation, scaffolding collaborative activities, and establishing netiquette guidelines are all important for facilitating productive collaboration.…”
Section: Incorporating Social Media In Teaching and Learningmentioning
confidence: 99%
“…Kummer's (2013) meta-analysis on wiki collaboration indicated that providing wiki training, incentivizing participation, scaffolding collaborative activities, and establishing netiquette guidelines are all important for facilitating productive collaboration. Multiple studies have suggested that, to optimally build collaborative knowledge, instructors must integrate scaffolding, class discussions, and multiple time points of graded feedback (Lin & Reigeluth, 2016, 2019. The scientific memes assignment integrates similar characteristics to optimize student learning outcomes (e.g., scaffolding, class discussions, and multiple graded feedback stages).…”
Section: Incorporating Social Media In Teaching and Learningmentioning
confidence: 99%
“…Asynchronous tools, such as online discussion forums, enable students to communicate at any time that suits them; forums, in particular are a popular way of supporting online group work (Oliveira, Tinoca, & Pereira, 2011). Wikis support collaborative writing, as well as other aspects of online collaboration (Lin & Reigeluth, 2016). Synchronous tools, such as Web conferencing, that support real-time audio, video and text interactions can also be valuable (Kear et al, 2010;Thorpe & Edmunds, 2011).…”
Section: Collaborationmentioning
confidence: 99%